Bear and bird : the picnic and other stories - Jarvis, 1985- (Somerville, Massachusetts : Candlewick Press, 2023)
Bear and Bird are best friends, and they spend a lot of time together. They don't always understand each other, but both agree that all they want is for their friend to be happy. So when Bear forgets the most important thing to pack for a picnic (but pretends that he didn't), Bird doesn't let on that she knew all along. And when Bird is upset to discover her friend has more of a certain talent than she does, Bear finds a touching way to make her feel better.